SOME ASPECTS OF AGRICULTURAL DEVELOPMENT FUND FOR THE CITY OF NIS IN 2011 - Simonović, Zoran; Simonović, Dragoljub; Miletić, Slavomir (Economics of Agriculture, 2011)
Under modern conditions in which we live emerges is an increasing need to address the problem of rural development. The last reform of the Common Agricultural Policy of the European Union is increasingly devoted attention to the issue of agricultural environment and its planning perspective. This approach stems from new features rural areas. Rural cannot be identifed because the agrarian diversifcation takes place in rural areas. The process of revival of rural settlements and paying increasing attention to environmental protection and enhancement of agricultural production may slow the reduction of agricultural settlements. Just to revive the rural settlements are made of agricultural development programs. This paper is primarily interested in the program of agricultural.